Teaching fractions at elementary level in the light of Hungarian mathematics textbooks in Romania - Baranyai, Tünde Klára (Teaching Mathematics and Computer Science, 2024)
According to the new curriculum in Romania, fractions are introduced in the second grade. The present study analyses Hungarian elementary mathematics textbooks on the topic of fractions focusing on the types of tasks in the textbooks, the significance of representations and the proportion of word problems. Additionally, the paper presents a questionnaire-based research on teachers’ opinion regarding the adequacy and sufficiency of the digital materials and exercises related to fractions in the textbooks. Subject Classification: 97F40, 97F80, 97U20, 97U50